Diversity policies meet the competency movement: towards reshaping law firm partnership models for the future. Issue 1 (2nd January 2018) - Seuffert, Nan; Mundy, Trish; Price, Susan
ABSTRACT: Globalisation, commercialisation, and economic pressures following the global financial crisis have produced a 'new normal' for the practice of law in private firms, requiring reassessment of the range of skills necessary for success. Scholarship in the 'competencies movement' has responded to this need for skills reassessment. At the same time, research and scholarship focused on increasing diversity and inclusion in law firms has blossomed. However, little attention has been paid to analysing synergies in the competencies and diversity movements, and there have been calls for more collaborative research between academics, firms and professional bodies in response to issues of diversity and inclusion. This article presents a collaborative research project between law firms, the Women Lawyers Association of New South Wales, and the Legal Intersections Research Centre at the University of Wollongong on current best practices in diversity in large Australian law firms. It argues that such collaborative projects, with a focus on synergies between the competencies and diversities movements, provide the greatest potential for reshaping law firm practice and partnership models to respond to issues of advancement, attrition, and lack of re-engagement, particularly by women in law firms.